Corrective vs. Distributive Justice: the Case of Apologies - Cohen, Andrew I. (Ethical theory and moral practice, 2016)
This paper considers the relation of corrective to distributive justice. I discuss the shortfalls of one sort of account that holds these are independent domains of justice. To support a more modest claim that these are sometimes independent domains of justice, I focus instead on the case of apologies. Apologies are sometimes among the measures specified by corrective justice. I argue that the sorts of injustices that apologies can help to correct need not always be departures from ideals specified by distributive justice. Apologies and the moral relations they engage might thus be parts of a domain of justice that is neither distributive nor dependent on distributive justice.